Fluorescent bioinspired albumin/polydopamine nanoparticles and their interactions with Escherichia coli cells - Equy, Eloïse; Hirtzel, Jordana; Hellé, Sophie; Heurtault, Béatrice; Mathieu, Eric; Rabineau, Morgane; Ball, Vincent; Ploux, Lydie (Beilstein Journal of Nanotechnology, 2023)
Inspired by the eumelanin aggregates in human skin, polydopamine nanoparticles (PDA NPs) are promising nanovectors for biomedical applications, especially because of their biocompatibility. We synthesized and characterized fluorescent PDA NPs of 10–25 nm diameter based on a protein containing a lysine–glutamate diad (bovine serum albumin, BSA) and determined whether they can penetrate and accumulate in bacterial cells to serve as a marker or drug nanocarrier. Three fluorescent PDA NPs were designed to allow for tracking in three different wavelength ranges by oxidizing BSA/PDA NPs (Ox-BSA/PDA NPs) or labelling with fluorescein 5-isothiocyanate (FITC-BSA/PDA NPs) or rhodamine B isothiocyanate (RhBITC-BSA/PDA NPs). FITC-BSA/PDA NPs and RhBITC-BSA/PDA NPs penetrated and accumulated in both cell wall and inner compartments of Escherichia coli (E. coli) cells. The fluorescence signals were diffuse or displayed aggregate-like patterns with both labelled NPs and free dyes. RhBITC-BSA/PDA NPs led to the most intense fluorescence in cells. Penetration and accumulation of NPs was not accompanied by a bactericidal or inhibitory effect of growth as demonstrated with the Gram-negative E. coli species and confirmed with a Gram-positive bacterial species (Staphylococcus aureus). Altogether, these results allow us to envisage the use of labelled BSA/PDA NPs to track bacteria and carry drugs in the core of bacterial cells.
Keywords: accumulation; albumin; antibacterial; Escherichia coli; fluorescence; nanoparticles; penetration; polydopamine